2011
DOI: 10.1002/ajh.22201
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated doses of gemtuzumab ozogamicin with escalated doses of daunorubicin and cytarabine as first acute myeloid leukemia salvage in patients aged 50–70‐year old: A phase 1/2 study of the acute leukemia French association

Abstract: This Phase 1/2 study aimed to determine optimal doses of daunorubicin (DNR; mg/m 2 ) and cytarabine (mg/m 2 ) to be combined with fractionated doses of gemtuzumab ozogamicin (GO, Mylotarg 1 ; 3 mg/m 2 on day 1, 4, and 7) satisfying safety requirements. Three dose levels of DNR/AraC were investigated namely (45, 100), (60, 100), and (60, 200). Patients included were acute myeloid leukemia in first relapse, aged 50-70 years. Hematological recovery was 31 days for neutrophil and 32 days for platelet counts. A doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…CR rates between 32% and 55% were observed for combinations of GO with chemotherapy. [91][92][93] Interestingly, data from the MRC 15 trial showed that the addition of GO to induction therapy might be of significant benefit for patients with CBF AML. 94 Although GO is not easily available outside clinical trials, we try to get this drug based on published evidence in elderly relapsed patients with CD33 expression of the blasts as a bridge to transplantation.…”
Section: Targeting Cd33mentioning
confidence: 99%
“…CR rates between 32% and 55% were observed for combinations of GO with chemotherapy. [91][92][93] Interestingly, data from the MRC 15 trial showed that the addition of GO to induction therapy might be of significant benefit for patients with CBF AML. 94 Although GO is not easily available outside clinical trials, we try to get this drug based on published evidence in elderly relapsed patients with CD33 expression of the blasts as a bridge to transplantation.…”
Section: Targeting Cd33mentioning
confidence: 99%
“…104,105 This observation suggests that repeated administration of lower, (near-)saturating doses of GO every 3 days may enhance intracellular accumulation of the calicheamicin-␥ 1 derivative beyond what can be achieved with 2-weekly administration. The Acute Leukemia French Association group has relatively recently reported the use of GO in fractionated, lower doses with promising efficacy and acceptable safety profile, 89,106 but comparative data with the traditional administration scheme are currently not available.…”
Section: Clinical Experience With Gomentioning
confidence: 99%
“…GO at 3 mg/m 2 given on Days 1, 4 and 7) has been pioneered by the French ALFA group and revealed a favorable efficacy/toxicity profile. [22][23][24] For example, among 57 patients with AML in first relapse, GO monotherapy given in fractionated doses resulted in 15 (26%) CRs and 4 (7%) CRs with incomplete platelet recovery (CRps). Interestingly, relative to our study, the study by Taksin et al included adults of all ages requiring therapy for AML in first relapse with a CR duration of at least three and up to 18 months, 22 i.e.…”
Section: Discussionmentioning
confidence: 99%